Back Cover: A Combined Bioinformatics and Chemoinformatics Approach for Developing Asymmetric Bivalent AMPA Receptor Positive Allosteric Modulators as Neuroprotective Agents (ChemMedChem 2/2013). Issue 2 (28th January 2013) - Chen, Haijun; Wang, Cheng Z.; Ding, Chunyong; Wild, Christopher; Copits, Bryan; Swanson, Geoffrey T.; Johnson, Kenneth M.; Zhou, Jia
<x xml:space="preserve">Abstract</x> The back cover picture shows the rational design of asymmetric bivalent positive allosteric modulators (PAMs) of the α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor by using an effective, combined bio‐ and chemoinformatic approach. These ligands display marked potency in vitro and efficacy in vivo for preventing neuroapoptosis. For more details, see the Communication by Jia Zhou et al. on p. 226 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>